Multimorbidity Among Patients Receiving Home Care in Japan: Prevalence, Levels, and Association With Emergency Home Visits - Gen Nakayama; Shoichi Masumoto; Yu Sun; Mitsuaki Ishii; Sayaka Nin; Takashi Inaba; Natsuki Kajikawa; Shuhei Hamada; Noriyuki Kimura; Jun Hamano (Journal of General and Family Medicine, 2026)
ABSTRACT Background Despite its clinical importance in primary care, the prevalence and levels of multimorbidity among patients receiving home‐based medical care remain poorly characterized, and its potential impact on emergency home visits is unclear. This study described the prevalence and levels of multimorbidity among patients receiving physician‐led home care in Japan and examined the association between multimorbidity level and emergency home visits. Methods A multicenter cross‐sectional study was conducted in 2024 using physician‐completed questionnaires derived from medical records. Multimorbidity was defined as the presence of two or more chronic conditions. Based on prior literature, multimorbidity level was categorized as low (2–3 conditions), medium (4–5 conditions), or high (≥ 6 conditions). The primary outcome was the occurrence of an emergency home visit within the preceding month. Results Among 506 included patients, 94.7% met criteria for multimorbidity, and 13.2% required an emergency home visit. In multivariable generalized linear mixed‐effects models with a logit link, higher multimorbidity levels were independently associated with increased odds of emergency home visits, with adjusted odds ratios of 2.16 (95% CI, 1.09–4.31) for the medium‐level group and 2.72 (95% CI, 1.19–6.19) for the high‐level group compared with the low‐level group. Conclusions Multimorbidity was highly prevalent among Japanese patients receiving home care, exceeding prior domestic estimates while aligning with international reports. Higher levels of multimorbidity were associated with an increased likelihood of emergency home visits, suggesting that assessment of multimorbidity level may, if confirmed in future studies, inform risk stratification and policy planning for home‐based care services. Trial Registration UMIN000056282